Job stress and the factors that influenced job stress in company Jati Beringin Sdn Bhd / Aisya Deelaila Mohd Nasir - Mohd Nasir, Aisya Deelaila (Faculty of Business and Management, 2014)
These researches were focus on topic level of stress in organizations which it is important to maintain company performance in order to achieve company goals through its employees itself. The ability of any organization to channel its organizational goals is to retain valuable employees in organization. Therefore, in order to investigate best factor that contribute motivation among employees, the focus of this study will be identifying the level of job stress among employees at private sector.